Hereditary hemorrhagic telangiectasia: First demonstration of a founder effect in Italy; the ACVRL1 c.289_294del variant originated in the country of Bergamo 200 years ago. Issue 8 (27th May 2022) - Sbalchiero, Anna; Abu Hweij, Yasmin; Mazza, Tommaso; Buscarini, Elisabetta; Scotti, Claudia; Pagella, Fabio; Manfredi, Guido; Matti, Elina; Spinozzi, Giuseppe; Olivieri, Carla
Abstract: Background: Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant vascular disorder, affecting 1:5000 individuals worldwide. All the genes associated to the disease ( ENG, ACVRL1, SMAD4, GDF2 ) belong to the TGF‐β/BMPs signaling pathway. We found 19 HHT unrelated families, coming from a Northern Italy region and sharing the ACVRL1 in‐frame deletion c.289_294del (p.H97_N98). Methods: To test the hypothesis of a founder effect, we analyzed 88 subjects from 19 families (66 variant carriers, showing clinical signs of HHT, and 22 non‐carriers, unaffected) using eight microsatellite markers within 3.7 Mb around the ACVRL1 locus. After the haplotype reconstruction, age estimation of the variant was carried out. Results: We observed a common disease haplotype in 16/19 families, while three families showed evidence of recombination around the ACVRL1 locus. The subsequent age estimation analyses suggested that the mutation occurred about 8 generations ago, corresponding to about 200 years ago. We also present novel in silico and modeling data supporting the variant pathogenicity: the deletion alters the protein stability and removes the unique extracellular glycosylation site. Conclusion: We have demonstrated, for the first time, a "founder effect" for a HHT pathogenic variant in Italy. Abstract : We analysed 19 HHT unrelated families: a total of 66 affected patients carrying the ACVRL1 c.289_294del variant and 22 unaffected relatives.